FACTORS RESPONSIBLE FOR LOW CONVICTION OF CHILD SEXUAL ABUSE OFFENDERS- LUSAKA DISTRICT, ZAMBIA - Mevryn Musonda Mwewa; Qinglin Zhang; Imasiku. L. Mwiya (European Scientific Journal, ESJ, 2015)
Child Sexual Abuse (CSA) is a worldwide phenomenon which has evolved from a matter of family to public concern. Numerous researches have demonstrated tremendous after-effects inclusive but not limited to psychological and physical. The international community, Zambia included battles to combat this ravaging scourge. Prosecution of offenders has reemerged as a measure to stop CSA. This study examined factors responsible for low conviction of offenders of CSA in the face of substantial evidence. Survey design using qualitative methods: a questionnaire, semi structured interview and participant observation methods were used to conduct the study. The results showed: absence of technical knowledge of child psychology in courtrooms, an adversarial court system, official’s lack of skills and training, understaffing and poverty, contribute to the failure to convict offenders.